Optimal coordination of overcurrent relay protection using evolutionary programming / Noor Shah Rizal Abdul Manap - Noor Shah Rizal, Abdul Manap (2018)
Protection of distribution system is one of the major significant elements in power systems. Overcurrent relay is one of most commonly used protective relays and commonly used for the protection of ring and radial sub transmission systems, and distribution systems. Directional overcurrent relay is mainly used for the primary protection of ring distribution systems as the same magnitude of fault current can flow in either direction. In the distribution system, the protection relay is one of the equipment in the system that can detect from any abnormal activity and protect the area under its observation. The time coordination between protection relay need to be at minimum of time interruption. Hence, the optimum setting for all coordination protection relay is necessary to protect the system from any electrical fault and disturbance. Some researches have been carried out on coordination of overcurrent relays. Due to the difficulty of existing techniques employing different types of algorithm, the usual optimal coordination of overcurrent relays is generally carried out by heuristic, meta-heuristic optimization methods. Therefore, this research employed a metaheuristic optimization for Evolutionary Programming (EP) to find the optimum time for optimization overcurrent protection relay in radial distribution system. The optimum time for each relay during the fault occurrence is the obtained from the optimization process. This meta-heuristic method is selected as it has less parameters to be adjusted and computationally simple to adopt with the coordination problem. The performance of the applied method is tested on 3-bus radial system with different load current. The obtained results are compared with the reference case study.